Antifungal properties of cassava starch edible film incorporated with lemongrass essential oil - YULIA ANNISA; ISMAIL SULAIMAN; NOVI SAFRIANI; M. DANI SUPARDAN (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2014)
The aim of this study was to evaluate the antifungal properties of cassava edible film incorporated with lemongrass essential oil against two strains of fungal, Trichoderma sp and Penicillium sp. Edible films were prepared from a mixture of cassava starch and glycerol. Lemongrass oil (0.5%, 1%, 2%, 3% and 4% w/w) was added to edible films as natural antifungal agent. The agar disc diffusion method was used to determine the antifungal activity of cassava starch edible film. Antifungal behaviour was determined by the mold absences upon the film and by the inhibition zone formed. The experimental results showed that Trichoderma sp and Penicillium sp was not appear above the film until the fourth day. However, cassava starch edible films containing lemongrass oil did form any inhibition zone toward both of fungal